Maternal serum C - reactive protein and fibrinogen concentration in women with pre-eclampsia - Mohammad Abedi Samakoosh; Shahla Yazdani; Zinatosadat Bouzari; Masoumeh Golsorkhtabaramiri (Caspian Journal of Reproductive Medicine, 2015)
Background: Despite many studies published in recent years concerning pathogenic mechanisms of pre-eclampsia, but this issue remains controversial. The aim of the present study was to compare C-reactive protein (CRP) level and fibrinogen concentration obtained from pregnant women with pre-eclampsia with those obtained from women with normal pregnancies.